Changing littering behavior among university students in Egypt: Integration of community readiness and community-based social marketing - Torky, Nevin (AUC Knowledge Fountain, 2017)
Litter is simultaneously the most ignored and most visible form of environment degradation and is harmful to the health of humans and wildlife. The littering problem in Egypt is a major issue that can be seen in most of Egyptian neighborhoods. Many countries are working on litter reduction strategies, studies and programs to be litter free countries. In Egypt, there is almost no literature or national initiatives that address littering. There is an obvious need to study littering behavior and develop intervention programs to reduce litter in Egyptian communities. This study aims to help to change adult littering behavior as well as provide potential recommendations for future anti-littering efforts in two Egyptian universities. The first goal of this research is to identify the unique characteristics of the students in both universities and their level of readiness to change littering behavior in their universities by using the Community Readiness Model (CRM). The second aim is to use this information in planning for effective littering prevention programs to be implemented in the future in both universities by using Community- Based Social Marketing (CBSM). The CRM is an efficient and innovative tool for characterizing and assessing the level of readiness of a community to take action on an issue. In this study, CRM assessed the students' knowledge about littering problem and the exiting littering prevention efforts and their characteristics, capacities and commitment to change littering behavior. Each university receives one of the nine stages of community readiness, and overall strategies for conducting littering prevention programs are recommended accordingly. The CBSM is also a useful tool for fostering behavior change by identifying the barriers to a behavior and developing programs to overcome these barriers. This study is analyzing the perceived barriers to design littering prevention strategies and activities that address these barriers.The results indicated that both universities are at the "Initiation" stage of readiness to change littering behavior. Strategies were recommended to reduce littering that match the level of readiness within both universities and possible CBSM tools were suggested to address the barriers found in both universities.